Synthesis and Evaluation of the Cytotoxic Activity of Water-Soluble Cationic Organometallic Complexes of the Type [Pt(η1-C2H4OMe)(L)(Phen)]+ (L = NH3, DMSO; Phen = 1,10-Phenanthroline) - Federica De Castro; Erika Stefàno; Danilo Migoni; Giorgia N. Iaconisi; Antonella Muscella; Santo Marsigliante; Michele Benedetti; Francesco P. Fanizzi (MDPI AG, 2021)
Starting from the [PtCl(η1-C2H4OMe)(phen)] (phen = 1,10-phenanthroline, 1) platinum(II) precursor, we synthesized and characterized by multinuclear NMR new [Pt(η1-C2H4OMe)(L)(phen)]+ (L = NH3, 2; DMSO, 3) complexes. These organometallic species, potentially able to interact with cell membrane organic cation transporters (OCT), violating some of the classical rules for antitumor activity of cisplatin analogues, were evaluated for their cytotoxicity. Interestingly, despite both complexes 2 and 3 resulting in greater cell uptake than cisplatin in selected tumor cell lines, only 3 showed comparable or higher antitumor activity. General low cytotoxicity of complex 2 in the tested cell lines (SH-SY5Y, SK-OV-3, Hep-G2, Caco-2, HeLa, MCF-7, MG-63, ZL-65) appeared to depend on its stability towards solvolysis in neutral water, as assessed by NMR monitoring. Differently, the [Pt(η1-C2H4OMe)(DMSO)(phen)]+ (3) complex was easily hydrolyzed in neutral water, resulting in a comparable or higher cytotoxicity in cancer cells with respect to cisplatin. Further, both IC50 values and the uptake profiles of the active complex appeared quite different in the used cell lines, suggesting the occurrence of diversified biological effects. Nevertheless, further studies on the metabolism of complex 3 should be performed before planning its possible use in tissue- and tumor-specific drug design.